2008
DOI: 10.1155/2008/845674
|View full text |Cite
|
Sign up to set email alerts
|

Pain Catastrophizing Scale for Francophone Adolescents: A Preliminary Validation

Abstract: The results suggest that the PCS-Ado is valid and reliable with francophone adolescents. Further research is required to assess the validity of the PCS-Ado in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 50 publications
7
36
2
1
Order By: Relevance
“…The internal consistency for all subsections (rumination, helplessness and magnification) of the SA-PCS was also found to be excellent and considerably higher than previously reported ICC’s for subsections of the PCS. Nevertheless, the high internal consistency for the subsection magnification of the English, Afrikaans and Xhosa SA-PCS (α = 0.96; 0.99 and 0.93 respectively) found in this study is contradictory to the majority of validation studies which have previously reported that internal consistency for the magnification subsection, in particular, is usually unsatisfactory [7,34,37,38,40,41]. The internal consistency reported for the subsection magnification of the original, French, French-Canadian, Catalan, Italian and German PCS ranged between α = 0.56 to 0.67.…”
Section: Discussioncontrasting
confidence: 99%
“…The internal consistency for all subsections (rumination, helplessness and magnification) of the SA-PCS was also found to be excellent and considerably higher than previously reported ICC’s for subsections of the PCS. Nevertheless, the high internal consistency for the subsection magnification of the English, Afrikaans and Xhosa SA-PCS (α = 0.96; 0.99 and 0.93 respectively) found in this study is contradictory to the majority of validation studies which have previously reported that internal consistency for the magnification subsection, in particular, is usually unsatisfactory [7,34,37,38,40,41]. The internal consistency reported for the subsection magnification of the original, French, French-Canadian, Catalan, Italian and German PCS ranged between α = 0.56 to 0.67.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a similar difference is seen in the clinical samples, with our sample of headache sufferers scoring higher (M=33.35, SD=8.91) than the chronic pain sample of children recruited by Crombez et al [4] from a pediatric pain ward for evaluation of psychological problems (M=21.88, SD=11.44). The comparison with scores from the studies of Verwoort et al [30] documents even lower scores in the school sample than reflected in the data of Crombez et al [4] [13.27 (8.33)], whereas Tremblay et al [27] reported scores in between [22.56 (88.13)]. Thus the size of the scores varies considerably between studies conducted in different countries and on different samples.…”
Section: Discussionmentioning
confidence: 83%
“…PCS scores have been found to reliably predict certain variables, such as severe pain, disability, and emotional disturbances, which occur following trauma or tissue damage (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%